INCREASED KNOWLEDGE AND MOTIVATION FOR PREGNANT MOTHERS IN DETECTING STUNTED PREMATURE APPLICATIONS USING WEB-BASED STUNTING (WARD ACTION) FORMS - hasanah, intan nugraheni; Widyawati, Melyana Nurul; Octaviani, Dhita Aulia (Postgraduate Program , Poltekkes Kemenkes Semarang, 2024)
Background: Stunting is a chronic undernourishment problem caused by chronic insufficient nutrition intake through a food supply that fails to meet the nutritional needs that occur while the fetus is still in the womb. Knowledge and motivation for an expectant mother are among the challenges of stunting prevention, so a collective effort is required to increase your knowledge and literacy in stunting prevention. Specific nutrition intervention efforts are being made to achieve 3.0% per year, or 14% by 2024. Using information technology through smartphones as social media for early stunting detection is expected to increase maternal knowledge and motivation to detect stunting. Methods: The study is a quasi study of experiments using the design of one group pre-post test. The population in this study is expectant mothers in the region of central kesmas now the city of semarang. Sampling in this study USES an impressive sample. The number of samples of the treatment group was 215 expectant mothers who were determined to use the sample count formula. Research instruments use a questionnaire on the web application. Results: Research shows that most of the respondents are 20-35 years old, with their last level of education: high school /SMK/ equality, working, level > 150 cm, pregnancy distance > 2 years and have normal hb levels. There is an increased knowledge of stunting concepts and motivations in pregnant mothers before and after interventions using web-based